Evaluation Of The Pest Rat Census Sample Method (Rattus Sp.) at Sei Merah Estate PT. PP London Sumatera Indonesia Tbk - Adi Prima Saragih; Ahmad Saleh; Guntoro Guntoro (Jurnal Agro Estate, 2018)
The most damaging mammalian pests of oil palm plants are rats consisting of house mice (Rattus diardii), rice mice (Rattus argentiventer), and tree rats (Rattus tiomanicus). In controlling rat pest, a census is needed as a guideline for implementing good control. The common census method applied on plantations is 5% of the sample area, but there are obstacles in the implementation for high plants, and rat sporadic attacks. This research was conducted in May - July 2018 at Sei Merah Field with descriptive and correlation techniques. This study aims to evaluate census sample methods, at different attack rates. Another goal is to determine one indication of rat's attacked to represent other indications as a reference for the census method. Observation was made with a census of 100% (whole) trees in the 3 speciﬁed areas. Attacked tree category is if there was a damage on the fruit on the tree, the loose fruit (brondolan), and the male ﬂowers on the tree. Then 100% census observation compared to the 50%, 30%, 20%, 10%, and 5% rate samples. The results of the observation showed that the census sample method carried out using a 5% sample was declared eﬀective, because the regression ratio of the results of 5% rate sample (0.90) was not diﬀerent from the regression of 100% rate sample (1.00) and indications of the tree that attacked by rats on oil palm.